(untitled) (Perner’s Contacts, 2013)
The article deals with new technologies of so called "green moving" and analyses the technology WheelTug which should, according to its producer, help to develop ground air traffic not only from the point of view of economy, safety and operation, but also from the point of view of ecology. As WheelTug technology has not been put into real operation yet, measuring operational costs in land operation comes from testing procedures and simulation program.